The Development and Application of Biosensors in Medical Diagnostics in Indonesia - Sabrina Hayati; Abdul Karim (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Biosensors are analytical devices that combine biological sensing elements with physicochemical detectors to provide rapid, accurate, and cost-effective solutions for medical diagnostics. Globally, these devices have revolutionized the detection and monitoring of diseases, significantly impacting patient outcomes. In Indonesia, the adoption and development of biosensor technology have accelerated over the past decade, particularly in response to the growing healthcare needs and the government's push for technological innovation. This study aims to review and analyze the development and application of biosensors in Indonesia medical diagnostics sector between 2014 and 2024. The research focuses on identifying key technological advancements, the integration of biosensors into healthcare, the challenges faced in their development and deployment, and the prospects for future growth. The study employs a comprehensive literature review and analysis of scientific publications, industry reports, and government documents related to biosensor technology in Indonesia. The review covers the evolution of biosensing materials, point-of-care testing applications, integration with digital health technologies, and regulatory frameworks. Data were synthesized to provide a detailed overview of the current state of biosensor technology and its impact on medical diagnostics in Indonesia. The findings indicate significant advancements in biosensor technology, particularly in the development of novel nanomaterials, the integration of biosensors with mobile health (mHealth) platforms, and the expansion of point-of-care testing (POCT) for infectious diseases. However, the sector faces challenges, including technological limitations, regulatory hurdles, and economic constraints, which have slowed the widespread adoption of biosensors in clinical settings. Despite these challenges, the future of biosensors in Indonesia appears promising, with continued investment and innovation expected to drive further advancements in this field.